New public management and the ‘business’ of policing organised crime in Australia - Mann, Monique (Criminology & criminal justice, 2017)
The globalisation of new public management (NPM) across OECD countries had a profound impact on the administration and management of policing policy and practice. The ideologies of NPM were enthusiastically embraced in Australia in response to high-level corruption with mixed results. This article draws on interviews with senior Australian federal police to explore the policing of organised crime in the context of NPM. Emerging themes concerned the requirement to make the ‘business case’ for resources on the basis of strategic intelligence, recognition of the complexities associated with performance measurement and institutional competition as agencies vie for limited public resources. This article questions the discursive practices of NPM policing and raises questions about notions of ‘accountability’ and ‘transparency’ for effective police approaches to organised crime.